Ocena jakości życia pacjentów z jaskrą - Jurowska-Liput, Joanna; Niżankowska, Maria Hanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Glaucoma as a chronic and often asymptomatic disease in its early stages has a great influence on Quality of Life (QOL). Mostly because of disturbances in visual functions like damage to the visual field, lower visual acuity, the psychological impact of the diagnosis, side effects and the cost of treatment. Evaluation of QOL is very useful instrument which helps to decide about the ways of treatment. Especially if they are equally beneficial but have totally different psychological impact. Considering patients’ needs, satisfying their expectations and education, there is a guarantee of keeping the therapeutic indications and high efficiency of treatment.